Strategic control and its impact on the performance of the insurance company: Applied research in the Iraqi insurance company (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:               The current research aims to demonstrate the relationship of correlation and influence between the independent variable strategic control through its dimensions represented by (organizational structure, human resources management, commitment to specialization, defining powers and responsibilities, values and integrity) and the dependent variable the performance of the insurance company, and the degree of arrangement of these dimensions according to their importance, as well as Detection of significant differences in the sample's response to the questionnaire paragraphs in the researched company, and the research problem was identified in the main question: Is there a role for strategic control in the performance of the researched company? The analytical descriptive approach was relied upon, and the questionnaire was used as a means to obtain data from the (102) sample. Individuals from the employees of the researched company, in addition to conducting personal interviews with its officials, and the data was analyzed based on the statistical program (SPSS V.18), in calculating (weighted arithmetic mean, standard deviation, coefficient of variation, Pearson correlation coefficient, regression coefficient, coefficient of determination R², test F, exploratory factor analysis), and the research reached a set of results, the most prominent of which was the existence of a correlation and effect Significant of strategic control in the performance of the researched company, as well as the absence of significant differences in the sample's answers to the questionnaire items according to personal variables.